Managing Finances for Family Education amidst the COVID-19 Pandemic and its Consequences - Syaifullah M. Syam; Zaifullah Zaifullah (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
This study investigates the management of family education expenses in the context of the COVID-19 epidemic and assesses the subsequent social and economic implications. The study was conducted in the Central Sulawesi village of Pasigala using a qualitative research approach and a factual exposure standpoint. The data collection process used methods like observation, interviews, and documentation. Subsequently, the gathered data underwent analysis using the Miles and Huberman model, encompassing data reduction, presentation, and verification. The research outcomes underscore the significance of effective financial management in meeting familial, educational, and financial obligations during the COVID-19 pandemic. Additionally, the pandemic has notably affected social dynamics and economic conditions. Socially, there has been a shift in values and behaviors among the population, while economically, there has been a decline in individuals' income. These findings lead to the conclusion that the COVID-19 pandemic has indeed influenced the financial management of family education. Consequently, the study recommends implementing robust financial management practices in family education to ensure resilience in facing unforeseen challenges.